PENINGKATAN HASIL BELAJAR MELALUI MODEL PROBLEM BASED LEARNING MENGGUNAKAN GOOGLE CLASSROOM MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM SISWA KELAS XII IIK 2 ERA PANDEMI MAN 4 JOMBANG - Nuriana, Fatatin (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
In the era of the covid 19 pandemic, all activities including learning must be done from home. As a result, not a few students' learning outcomes are low. One of the factors is the implementation of models and the use of learning media, especially in the Islamic Culture History Subject. Thus, educators must develop creativity and innovate in learning by utilizing technology with google classroom as an online learning medium and present interesting learning models such as problem based learning models. The results of this research are: 1) planning the use of google classroom to improving learning outcomes of problem.based.learning models,.is by compiling lesson plans, compiling teaching materials, preparing teaching media, and making learning outcomes measuring tools. 2) implementation the use of google classroom to improving learning outcomes of the problem based learning model was carried out in 2 cycle stages with pre action pretest, posttest in cycles I and II. 3) evaluation the use of google classroom to improving learning outcomes of the problem.based.learning.model there is an increase in learning outcomes from pretest to cycle I with average values, namely pretest (67,5), posttest cycle I (75) and posttest cycle II (93,5). Abstrak Di era pandemi covid 19, segala aktivitas termasuk pembelajaran harus dilakukan dari rumah. Akibatnya, tidak sedikit hasil belajar peserta didik menjadi rendah. Salah satu faktornya yaitu penerapan model dan penggunaan media pembelajaran, khususnya pada mata pelajaran SKI. Sehingga, pendidik harus mengembangkan kreativitas dan berinovasi dengan memanfaatkan teknologi dengan menggunakan google classroom sebagai media belajar daring dan menyuguhkan model pembelajaran menarik seperti model problem based learning. Hasil dari penelitian ini yaitu: 1) Perencanaan penggunaan google classroom dalam meningkatkan hasil belajar model problem based learning yaitu menyusun RPP, bahan/materi ajar, menyiapkan media ajar, dan membuat alat ukur hasil belajar. 2) Pelaksanaan penggunaan google classroom dalam meningkatkan hasil belajar model problem based learning dilakukan 2 tahap siklus dengan pra tindakan pretest dan posttest pasca tindakan di siklus I dan II, 3) Evaluasi penggunaan google classroom dalam meningkatkan hasil belajar model problem based learning ada peningkatan hasil belajar dari pretest hingga siklus I dengan nilai rata-rata, yaitu pretest (67,5), posttest siklus I (75) dan posttest siklus II (93,5).